As margens da ilegalidade : relações mercantis e sociais entre São Salvador Bahia e Buenos Aires (c. 1580 c. 1640) - Barros, Queila Guedes Feliciano (2013)
This study has as its main object of analysis and social market relations established between the port of Buenos Aires and Salvador Bahia, in the period of the Iberian Union. We undertook an analysis of the cyclical action of Iberian colonization in Brazil, comprising therefore a war for sugar and by trade with the River Plate as a major factor transformation of commercial and administrative reality of colonial Brazil. Having been the European manufacturing and enslaved blacks responsible for the largest share of exports from the port of Salvador Bahia, to the port of Buenos Aires, we investigate under what arrangements settled trade of such products in the Platine region, since, by law, were part of the forbidden and illegal. We ended up detecting that local practices in Buenos Aires, to "legalize the illegal" became a commercial culture itself, which nurtured colony in Brazil equal match, and the fruits of the earth rioplatense: wheat flour, suet and meat drought, largely consumed in Brazil and colony, through the port of San Salvador Bahia, fueled not only several ships that they made the trade in the Atlantic Ocean, as well as European possessions, linking well, Salvador Bahia and the port of Buenos Aires to circuits and connections Inter colonial mercantile, woven in the first half of the seventeenth century.